384 EFFECTS OF SOCIOECONOMIC STATUS AND CONTINUITY OF CARE ON OSTEOPOROSIS SCREENING. Issue 1 (1st January 2007) - Abernathy, E.; Tullo, T.; Ravakhah, K.; Cykert, S.
Abstract : Background: Less than half of eligible women are screened for osteoporosis despite funding for dual-energy x-ray absorptiometry (DEXA) scans by Medicare. In this study, we seek to identify factors associated with a lack of screening for osteoporosis. Methods: Women over age 65 were surveyed in a cross-sectional study regarding socioeconomic indicators, attitudes toward preventive screening, and healthy behaviors. Subsequent chart review revealed the number of women who had been screened for osteoporosis. Descriptive data were compiled, and bivariate analysis and logistic regression were performed with DEXA scan as the outcome of interest. Independent variables that were controlled for were income, education, race, age, and number of physicians seen in the past year. Results: We present preliminary results from 137 surveys and 122 chart reviews of women over 65 from 6 of 13 teaching centers. Sixty percent of patients had at least a high school education. Over half of patients (53%) earned less than $10, 000/year, over half (54%) were black, and 60% were widowed. Income ( p = .003), level of education ( p = .006), and visits with more than one physician ( p = .01) were associated with failure to have DEXA scans in bivariate analysis. Income remained a significant predictor of DEXA scan following multivariate analysis, with an odds ratio of 2.7, 95% CI [1.17-6.3]. Visits with greater than one physician likewise remained significant ( p = .04), with an odds ratio of 0.35, 95% CI [0.15-0.81] for receiving DEXA scan. Race was not significant in bivariate or multivariate analysis. Conclusions: In a group of patients with Medicare coverage, low income continued to be associated with decreased performance of osteoporosis screening. It is unclear whether socioeconomic status influenced physician or patient behavior or served as a barrier to obtaining DEXA scan (eg, transportation). Lack of continuity of care in this population also results in failure to receive appropriate osteoporosis screening. We continue to struggle with socioeconomic barriers to preventive screening even in a population in which the screening test is noninvasive and inexpensive to the patient.